The Effects of Cardiometabolic Factors on the Association Between Serum Uric Acid and Chronic Kidney Disease in Chinese Middle-Aged and Older Population: A Mediation Analysis - Xu, Lu; Sun, Hang; Liu, Lili; Zhan, Siyan; Wang, Shengfeng; Lv, Xiaozhen; Song, Yongfeng (Frontiers in Endocrinology, 2021)
Introduction: To explore whether dyslipidemia, hyperglycemia or hypertension has mediating effect on the association between serum uric acid (SUA) and the development of chronic kidney disease (CKD). Methods: We conducted a mediation analysis to explore the potential mediating effects of systolic blood pressure (SBP), diastolic blood pressure (DBP), blood glucose, triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) on the association between SUA and estimated glomerular filtration rate (eGFR). The data were obtained from China Health and Retirement Longitudinal Study (CHARLS), covering 5,762 individuals. Results: SUA had a negative dose-response total effect on eGFR (β -3.11, 95% CI -3.40 to -2.82, P-value<0.001). The linear regression between SUA and seven potential mediators indicated that blood glucose (β 0.80, 95% CI 0.18 to 1.42, P-value=0.012), TG (β 10.01, 95% CI 8.22 to 11.79, P-value<0.001), TC (β 2.64, 95% CI 1.83 to 3.45, P-value<0.001), HDL-C (β -0.27, 95% CI -0.52 to -0.02, P-value=0.034) and LDL-C (β 1.15, 95% CI 0.49 to 1.80, P-value=0.001) all had significant dose-response association with SUA, but SBP and DBP showed no significant association with SUA. In terms of the association between potential mediators and eGFR, only TG (β 0.003, 95% CI -0.001 to 0.01, P-value=0.117) and HDL-C (β 0.01, 95% CI -0.02 to 0.04, P-value=0.444) did not have significant linear association with eGFR. The linear regression showed that SUA was directly associated with eGFR (P-value<0.001). Conclusions: This study supported that the association between SUA and the risk of CKD was not mediated by hypertension, hyperglycemia or dyslipidemia.